A Discourse Analysis of Online Readers’ Comments on Political Discourse in Nigeria - Jibril, Abubakar; Idris, Sabiu; Mohammed, Adamu (UI Scholars Hub, 2022)
The internet has liberalized political discussion in Nigeria, and enhanced public debates on trending social, economic, religious, and political issues on the various platforms it harbours, such as the social media, online news sites and blogs among others. Online comments sections of news sites enable readers for instance, to discuss issues raised in the news from their individual points of view. This development facilitates interaction among news producers and consumers, and serves as effective feedback mechanism. However, previous researches have established disturbing trends on the platforms, bordering on a seaming inclination of discourse to ethnic, religious and regional schmaltziness. This portends damning implications on the age-long unity in diversity question in Nigeria. This study, therefore, undertakes a qualitative discourse analysis of comments on the various online news platforms vis-à-vis this ‘all important’ unity in diversity question. Specific attention was paid to the ideological leanings of the comments in terms of regional, ethnic and religious affiliations of commentators, with the aim to interrogate how these divides are forced into discourse on the platforms, and the implications on the unity and continuous corporate existence of the multicultural Nigeria.